2019
DOI: 10.1111/febs.14996
|View full text |Cite
|
Sign up to set email alerts
|

FRET‐based analysis and molecular modeling of the human GPN‐loop GTPases 1 and 3 heterodimer unveils a dominant‐negative protein complex

Abstract: GPN‐loop GTPases 1 and 3 are required for RNA polymerase II (RNAPII) nuclear import. Gpn1 and Gpn3 display some sequence similarity, physically associate, and their protein expression levels are mutually dependent in human cells. We performed here Fluorescence Resonance Energy Transfer (FRET), molecular modeling, and cell biology experiments to understand, and eventually disrupt, human Gpn1–Gpn3 interaction in live HEK293‐AD cells. Transiently expressed EYFP‐Gpn1 and Gpn3‐CFP generated a strong FRET signal, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…BioPlex 2.0 (47) predicted an interaction between RPA1 and GPN3 ( Figure S8A). This was interesting because GPN3, through a physical association with the related protein GPN1, associates with the Pol II complex and in some cells promotes assembly of functional Pol II in the nucleus (48)(49)(50)(51). GPN1 and GPN3…”
Section: Resultsmentioning
confidence: 99%
“…BioPlex 2.0 (47) predicted an interaction between RPA1 and GPN3 ( Figure S8A). This was interesting because GPN3, through a physical association with the related protein GPN1, associates with the Pol II complex and in some cells promotes assembly of functional Pol II in the nucleus (48)(49)(50)(51). GPN1 and GPN3…”
Section: Resultsmentioning
confidence: 99%
“…Gpn3 has been proposed to mediate RNA pols biogenesis, assembly, and transport to the nucleus ( Minaker et al, 2013 ; Liu et al, 2020 ) and has been demonstrated to form a stable complex with Gpn1 in both yeast and human ( Carre and Shiekhattar, 2011 ; Cristóbal-Mondragón et al, 2019 ; Liu et al, 2020 ). In addition, yeast gpn3 mutants mislocalize RNA pol II and III subunits, which suggests a role for Gpn3 (and Gpn2) in not only RNA pol II but also in RNA pol III assembly and/or transport ( Minaker et al, 2013 ).…”
Section: Assembly Factors Are Required For the Assembly Processes Of Rna Polymerasesmentioning
confidence: 99%
“…Gpn1, Gpn2, and Gpn3 are all essential proteins for cell growth, and deletion of each one results in cell death, suggesting that their functions are not redundant. Interestingly, Gpn1 and Gpn3 in mammalian cells are closely associated for RNAPII biogenesis regarding to protein level stability, mutual dependency, and genetic interaction 21‐24 . In the previous study, we identified yeast NPA3 and GPN3 as two multicopy genetic suppressors of gpn2 ts mutants 14 .…”
Section: Introductionmentioning
confidence: 98%
“…14 Here, we clearly showed that Gpn3 and Npa3 in yeast are mutually required to stabilize their protein levels ( Figure 4D,E), and that Gpn3 coordinates with Npa3 for RNAPII biogenesis. Although the association of Gpn1 with Gpn3 have been reported in human cells, 21,23 the specific role of Gpn3 in the biogenesis of RNAPII is not quite clear. Depletion of either Npa3 or Gpn3 leads to severe growth defects ( Figure 1A) indicates they are not redundant during RNAPII assembly.…”
mentioning
confidence: 99%
See 1 more Smart Citation